Characterization of drying paint coatings by dynamic speckle and holographic interferometry measurements - Budini, Nicolas (2016)
In this work we implemented dynamic speckle and holographic interferometry techniques to characterize the drying process of solvent-based paint coatings. We propose a simple way to estimate drying time by measuring speckle activity and incrementally fitting experimental data through standard regression algorithms. This allowed us predicting drying time after about 20-30 min of paint application, which is fast regarding usual times required to reach the so-called tack-free state (≈ 2 h). In turn, we used holographic interferometry to map small thickness variations of the coating surface during drying. We also demonstrate that results obtained from both techniques correlate to each other, which allows improvingthe accuracy of the drying time estimation.